ANALYSING RAINFALL FOR EFFECTIVE CROP PLANNING AND WATER MANAGEMENT IN GARIYABAND DISTRICT OF CHHATTISGARH PLAIN - Minj, Asha Kiran; Sahu, Dr. Sanddep; Yadaw, Dr. Praveen Kumar; Sahu, Dr. Lekhraj (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The volume and distribution of rainfall have a major impact on agricultural output. Rainfall statistics on a weekly, monthly, and seasonal basis are very useful for agricultural planning. With an emphasis on weekly, seasonal, and yearly rainfall, this study assesses the patterns of rainfall distribution in Gariyaband, Chhattisgarh, during a ten-year period (2011–2023). With an average of 104.6022 mm, the research shows that the 29th week of the monsoon season had the most rainfall, reaching 313.803 mm. According to monthly rainfall statistics, August had the most average rainfall of 299.1059 mm and November had the lowest, at 0.003628 mm. The highest amount of rainfall recorded in the Kharif season was 1437.004 mm, or 90.20% of the yearly average. With an average of 969.2082 mm, the monsoon season saw the most rainfall, while the winter season saw the least at 15.3071 mm. Runoff causes significant loss of rainfall, but it may be caught by employing in-situ or ex-situ water harvesting systems to be used in the summer, during Rabi and Kharif. In the rainy season, this water may also be used for irrigation that saves lives during dry spells, especially those that last one or two weeks and negatively impact standing Kharif crops. The variation in annual rainfall from the mean was -25.4% to +24.64%. The Gariyaband region's crop planning and the creation of water and soil conservation infrastructure can benefit from the knowledge gained from this rainfall research.